2020
DOI: 10.1037/pro0000278
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone psychology: New approaches towards safe and efficacious mobile mental health apps.

Abstract: Practicing psychologists are being faced with the reality that mobile mental health apps for smartphones and tablet devices are increasing in popularity. This growth area within e-mental health has been well documented in Professional Psychology: Research and Practice. This article provides an update on the issues of safety and efficacy in mental health app development, two of the biggest concerns that practicing psychologists have about these new digital tools. Governments and medical authorities are wrestlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…There are no known safeguards in place anywhere in the world to stop this from happening. While government agencies have started to regulate the health app space, this regulation has thus far focused on apps that only pose a risk of harm to users [ 62 ]. While this is important and a welcome addition to the oversight of mental health apps, it does not provide checks on accuracy of information in app store descriptions of apps that may not fall into the category of posing a risk of harm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no known safeguards in place anywhere in the world to stop this from happening. While government agencies have started to regulate the health app space, this regulation has thus far focused on apps that only pose a risk of harm to users [ 62 ]. While this is important and a welcome addition to the oversight of mental health apps, it does not provide checks on accuracy of information in app store descriptions of apps that may not fall into the category of posing a risk of harm.…”
Section: Discussionmentioning
confidence: 99%
“…However, the research found to accompany the apps listed here does appear to vary greatly in methodology; this reaffirms the claims of heterogeneity made in those literature reviews. These reviews all call for more research and ongoing evaluation of research methodology into studying apps, as the current methodologies may not be the most appropriate [ 62 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include the following: more economical for low socioeconomic groups to obtain mental health treatment compared with face-to-face services [ 69 ], improved access for those in rural areas where there may be limited treatment options [ 70 ], reduced stigma [ 71 ] because of anonymous assistance, access for children and adolescents who are already large consumers of smartphones and the internet [ 72 ], and it is simply a preferred way to receive mental health information for some [ 73 ]. Therefore, it is important to increase research on the efficacy and effectiveness of mental health apps using appropriate and scientifically validated methodologies in addition to RCTs, as the widely considered gold standard of RCTs may not be the most appropriate for analyzing mental health apps [ 23 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the time demands of the gold standard RCT can be an impediment to research, other methodologies that do not sacrifice scientific rigor and integrity can potentially be conducted on apps in a more timely manner (38). These include scalable single-case designs involving practicing clinicians working with researchers (36). In such a model, clinicians could contribute their findings to a centralized database that may continually be updated with results that occur from individuals using their app in real-world settings.…”
Section: Discussionmentioning
confidence: 99%